Natural regeneration in a restored bauxite mine in southeast Brazil - Miranda Neto, Aurino; Martins, Sebastião Venâncio; de Almeida Silva, Kelly; Teixeira Lopes, Aldo; de Abreu Demolinari, Raul (Bosque (Valdivia), 2017)
The objective of the present study was to verify if, in floristic terms of natural regeneration, a restored bauxite mine in southeast Brazil can be considered successfully restored. Forty plots of 3.0 x 3.0 m were allocated in the area. All shrubs and trees with height ≥ 0.30 m and diameter at 1.30 m height (DBH) ≤ 5.0 cm were identified and classified into successional categories and dispersal syndromes; DSL (diameter at soil level) and height were measured. We use the canonical correspondence analysis (CCA) to verify the correlations between environmental variables (canopy openness, litter decomposition, soil penetration resistance) and vegetation. We found 705 individuals, 80 species and 30 families. The families with the highest species richness were Fabaceae and Melastomataceae. The specie with the highest importance value (IV) was Myrcia splendens. Most species are the early secondary successional category and the zoochoric dispersion syndrome. CCA ordination indicates the formation of a group of species associated with less soil compaction and with low litter decomposition rate and the formation of another group associated with intermediate values of soil penetration resistance and litter decomposition rate. The results obtained after ten years of implementation of the restoration project, in floristic terms, are suitable. In other words, the area can be considered as successfully restored.